Les dérivés du nom propre Trump dans la presse française (2020–2021) : une analyse comparative des néologismes - Nekudová, Veronika (Verbum – Analecta Neolatina, 2024)
Donald Trump is still attracting a great deal of media attention: even after his term as president has ended, a large number of derivatives of his name are (re)appearing in the press. Three French daily newspapers were analysed to gain a better understanding of their structure and significance: Le Monde, Libération and Le Figaro. The studied corpus consists of a selection of articles published between March 2020 and February 2021 containing occurrences of derivatives of the proper name Trump. These data, collected during the year in which the presidential election and the assault on the Capitol took place, are used to compare the occurrences of neologisms formed from the proper noun Trump in the three newspapers, and attest to the semantic shifts in these new lexemes. They can therefore illustrate the underway trends and the mechanisms underlying all neologism creation.